Innovation-Investment Directions Of Business Processes In The Textile Industry - Zakirov Abduazim Abdurashidovich (Genius Publishing Group, 2023)
This article analyzes the essence of the innovation-investment direction, which is considered one of the important elements of business processes, and its current state in our practice.
Keywords: practice; important; innovation